KARAKTERISTIK SISTEM PEMBANGKIT LISTRIK TENAGA SURYA KAPASITAS 100 WP - Madona, Maisyara; Effendi, Asnal; Dasman, Dasman; Alfith, Alfith; Al, Al (ITP Press, 2024)
The energy crisis is a major problem in Indonesia, especially the problem of electrical energy. Electrical energy is energy that is important for humanity throughout the world. We can see from people's activities that cannot be separated from the use of electricity, such as the use of devices and technology that are currently used all using electricity. This phenomenon proves that electricity is very important and cannot be separated from community activities. For some time now, experts have changed their views regarding the use of energy resources in Indonesia. Be aware that fossil fuels, the main energy source, will be threatened with scarcity in the coming years. This research method uses a design/prototype method by making equipment and carrying out a series of tests and collecting data. Based on data that has been in sunny and cloudy weather, solar panels can produce the highest voltage of 17.79 which occurs between 12.30 to 16.30. while the lowest voltage produced by solar panels is around 12,6 Volts for the highest temperature of 34ºC for the highest current is 4,4 A and the highest light intensity is 64422 lux.